ITIKAD BAIK DALAM PERJANJIAN JUAL BELI TENAGA LISTRIK ANTARA PT. PERUSAHAAN LISTRIK NEGARA (PERSERO) DENGAN KONSUMEN - Rudyanti Dorotea Tobing (Jurnal Ilmu Hukum Tambun Bungai, 2017)
Electricity is one of the basic needs most needed by the community. Electric power has a very important and strategic role in realizing the goals of national development then the power supply business is controlled by the State In order for the community to enjoy electric power, the distribution of electricity is the power supply of electricity from the transmission system or from the generator to the consumer. This distribution is done through the sale of electric power, which is the business of selling electricity to consumers. The implementation of electricity sales business is carried out by State Owned Enterprises namely PT (limited liability company). PLN (State Electricity Enterprise) (Persero). If people are willing to buy electric power, then people must apply to PT. PLN (State Electricity Enterprise) (Persero). Furthermore, between PT PLN (State Electricity Enterprise) (Persero) and the society will be made a Letter of Sale and Purchase Power Agreement. As a effect of the law of the agreement, the contents of the agreement shall be executed by both parties. The parties shall enter into agreement in good faith. The principle of good faith can be deduced from Article 1338 Paragraph (3) of the Civil Code which states that "the Agreement shall be executed in good faith". The Agreement is made by normative and contains an exoneration clause. The rights and obligations of parties determined by PLN (State Electricity Enterprise) as the holder of the single electric power business in Indonesia, causing an injustice to the consumer. At the normative level in Act no. 30 Year 2009 on Electrification has seen there is good faith from the government to protect the interests of consumers (electricity customers). At the level of empirical position between consumers (electricity customers) with PT. PLN (State Electricity Enterprise) (Persero) is very unbalanced. PT PLN (Persero) is more dominant than consumers. PT. PLN (Persero) often does not perform its duties properly as regulated in the law because it feels to have the right of monopoly on the supply of electric power.